Enteral electrolyte solutions with different osmolarities administered in a continuous flow in newborn calves - José Dantas Ribeiro Filho (Ciência Rural, 2017)
This study compared the effects of enteral electrolyte solutions with different osmolarities in Holstein cattle. Eighteen newborn calves were evenly divided into three groups and administered the following treatments: hypotonic electrolyte solution (ESHYPO) containing 4g NaCl, 0.5g KCl, 1g sodium acetate, and 7.5g dextrose diluted in 1,000mL water; isotonic electrolyte solution (ESISO) containing 5g NaCl, 1g KCl, 2g sodium acetate, and 10g dextrose diluted in 1,000mL water; and hypertonic electrolyte solution (ESHYPER) containing 6g NaCl, 1g KCl, 3g sodium acetate, and 15g dextrose diluted in 1,000mL water. Solutions were administered at a rate of 15mL kg –1 hr –1 for 12 hours in a continuous flow. All three solutions increased the concentration of plasma sodium, but ESHYPO did not alter the serum osmolarity. Both ESISO and ESHYPO resulted in an increase in volemia.